Analysis of Reproductive Health Education Program for Adolescents in Secondary Schools - Astuti, Aurelia Widya (Al Makki Publisher, 2024)
Reproductive health education in secondary schools is very important considering the increasing rate of teenage pregnancy and the low knowledge of reproductive health among adolescents. This study aims to explore the effectiveness of reproductive health education programs implemented in these schools. This study aims to identify the materials taught, teaching methods used, as well as students' responses and perceptions of the reproductive health education program. The methods used in this study include in-depth interviews and focus group discussions (FGDs) with 60 students from three secondary schools in X city. Data were collected over two months and analyzed to find relevant patterns and themes. Findings showed that the education program improved students' knowledge of reproductive health, but there were challenges such as social stigma and variations in the quality of teaching. Students reported increased confidence and better understanding of reproductive health topics. Reproductive health education programs in secondary schools have significant potential to improve adolescent understanding, but improvements in materials, teaching methods, and social environmental support are needed to achieve optimal results.